2005
DOI: 10.1248/cpb.53.1043
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-(3-{4-[(3-Fluorobenzyl)oxy]phenoxy}propyl)-2-pyridin-4-ylacetamide as a Potent and Selective Reverse NCX Inhibitor

Abstract: Intracellular Ca2ϩ is of primary importance in the pathogenesis of ischemia and reperfusion injury in the myocardium. Recent studies have suggested that a massive Ca 2ϩ influx may occur as a consequence of Na ϩ -Ca 2ϩ exchange via the sodium-calcium exchanger (NCX) during reperfusion which, in turn, may be caused by an accumulation of Na ϩ via the sodium-hydrogen exchanger (NHE) during ischemia. 1,2)This results in an intracellular Ca 2ϩ overload, the detrimental effects of which include myocardial contracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The general consensus is that NCX1 inhibitors preferentially inhibit the inactivating Ca 2+ influx mode (RM) compared with the Ca 2+ efflux mode (FM) (13,1518) that displays no inactivation. We have recently reported that, in contrast to the cardiac NCX1.1 splice variant, β-cell NCX1 splice variants (NCX1.3 and -1.7) exhibit significant inactivation during FM operation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general consensus is that NCX1 inhibitors preferentially inhibit the inactivating Ca 2+ influx mode (RM) compared with the Ca 2+ efflux mode (FM) (13,1518) that displays no inactivation. We have recently reported that, in contrast to the cardiac NCX1.1 splice variant, β-cell NCX1 splice variants (NCX1.3 and -1.7) exhibit significant inactivation during FM operation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the identification of drugs with a greater selectivity for NCX1 inhibition over other ion transport pathways in the β-cell is a necessary first step in the advancement of β-cell NCX1 splice variants as novel therapeutic targets. In this latter regard, newer NCX inhibitors with a reported greater selectivity for NCX1 over other ion transport processes are in development for cardiovascular disease, and these inhibitors may also warrant further investigation for their splice variant selectivity and insulinotropic efficacy (13,1518). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deprotection of the methyl group of 16 was realized in 40% HBr Scheme 3. a) AlCl 3 (2.5 equiv), glutaric anhydride (1.0 equiv), anisole (excess), PhNO 2 , 100 o C, 3 h; b) H 2 (1 atm), Pd/C (10%), EtOH, rt, 12 h; c) 40% HBr, reflux, 12 h; d) H 2 SO 4 (1 drop/50 mL), EtOH, rt, 12 h; e) NaH (2.0 equiv), MOMCl (1.5 equiv), TBAB (0.06 equiv), THF, rt, 6 h; f) LiAlH 4 (1.0 equiv), THF, 0 °C to rt, 1 h; g) (COCl) 2 (2.0 equiv), DMSO (4.0 equiv), Et 3 N (8.0 equiv), CH 2 Cl 2 , -78 o C to rt, 15 min. aqueous according to the green procedure reported by Merschaert and co-workers [10] , and provided the desired product 17 with 95% yield after reflux for 12 h. Further esterification of 17 was promoted under sulfuric acid catalyzed condition and generated the known ester 18 [11] in 92% yield. The resulting phenol 18 was then subjected to MOM protection, LiAlH 4 reduction and Swern oxidation consequently to give targeted aldehyde 11 with 86% yield over 3 steps.…”
Section: Synthesis Of Aldehyde 11mentioning
confidence: 97%
“…1 H NMR (300 MHz, CDCl 3 ): δ = 7.10 (d, J = 8.7 Hz, 2 H), 6.96 (dd, J = 8.7 Hz, J = 2.0 Hz, 2 H), 5.16 (s, 2 H), 3.64 (t, J = 6.6 Hz, 2 H), 2.58 (t, J = 7.6 Hz, 2 H), 1.62 (m, 4 H), 1.41 (m, 2 H); 13 C NMR (75 MHz, CDCl 3 ): δ = 155. 3, 136.0, 129.3, 116.2, 94.6, 62.9, 55.9, 35.0, 32.6, 31.4, 25.3 (11). To a solution of oxalyl chloride (5.1 g, 40 mmol) in CH 2 Cl 2 (100 mL) was added a solution of DMSO (6.0 mL, 80 mmol) in CH 2 Cl 2 (6.0 mL) dropwise over 10 min at −78 °C.…”
Section: General Informationmentioning
confidence: 99%